The interaction between chromogranin A and catecholamines governs exocytosis. Issue 11 (30th July 2014) - Dominguez, Natalia; Estevez‐Herrera, Judith; Borges, Ricardo; Machado, Jose D.
Abstract : Chromogranins (Cgs) are acidic proteins that have been described in the large, dense core vesicles (LDCVs) of adrenal chromaffin cells and that have been shown to promote LDCV formation, even in nonsecretory cells. Catecholamines (CAs) are adsorbed by Cgs in vitro, and the absence of Cgs modifies the storage and exocytosis of CAs in chromaffin cells. In this study, we set out to assess the role of CgA in the accumulation and exocytosis of CAs in cells when the levels of CgA and CA are manipulated. We overexpressed CgA in nonsecretory HEK293 cells and in secretory PC12 cells, to study the formation, movement, and exocytosis of newly formed granules by evanescent wave microscopy. We analyzed the association of Cgs/CA by HPLC and amperometry and their role in the accumulation and exocytosis of amines, both under resting conditions and after l ‐DOPA overloading. To our knowledge, this is the first demonstration that CgA expression in a nonsecretory cell line facilitates the storage and exocytosis of CA. In addition, CgA overexpression causes a doubling of the accumulation of CA, although it slows down exocytosis in PC12 cells. We propose a model to explain how the CgA/CA complex governs the accumulation and exocytosis of secreted amines.—Dominguez, N., Estevez‐Herrera, J., Borges, R., Machado, J. D., The interaction between chromogranin A and catecholamines governs exocytosis. FASEB J. 28, 4657–4667 (2014). www.fasebj.org